Epidemiology, Associated Conditions, and Outcomes of Hospital Associated Vancomycin-Resistant Enterococcus Infections in the US Military Health Care System. (4th October 2017) - Stagliano, David; Susi, Apryl; Adams, Daniel; Nylund, Cade
Abstract: Background: Better strategies to combat vancomycin-resistant Enterococcus (VRE) infections are needed. Our study aims to characterize the epidemiology and associated conditions, and to measure the attributable cost, length of stay, and in-hospital mortality of VRE infections among hospitalized patients in the US military health system (MHS). Methods: We performed a retrospective cohort study of patients with VRE infections using MHS database billing records. Cases included all patients admitted to a military treatment facility for ≥2 days from October 2008 to September 2015 with a clinical culture growing Enterococcus faecalis, Enterococcus faecium or Enterococcus species (unidentified), reported as resistant to vancomycin. Comorbid conditions and procedures associated with VRE infection were identified by multivariable logistic regression. Patient case-mix adjusted outcomes including in-hospital mortality, length of stay, and hospitalization cost were evaluated by high-dimensional propensity score adjusted logistic regression. Results: During the 7-year study period and among 1, 161, 335 hospitalized patients within the MHS, we identified 577 (0.050%) patients with VRE infection. A majority of VRE infections were urinary tract infections (57.7%), followed by bloodstream (24.7%), other site/device-related (12.9%), respiratory (2.9%), and wound infections (1.8%). Risk factors for VRE infection included invasive gastrointestinal and urologic procedures, tracheostomy, as well as recent exposure to glycopeptides and extended-spectrum penicillins. Patients hospitalized with VRE infection had significantly higher hospitalization cost (attributable difference [AD] 117, 322, P < 0.001), prolonged hospital stay (AD 20.45 days, P < 0.001, and in-hospital mortality (case-mix adjusted odds ratio 5.77; 95% confidence interval 4.59–7.25). Conclusion: VRE infection in hospitalized patients is associated with an increased length of stay, hospital cost, and in-hospital mortality. Active surveillance and infection control efforts should target those identified as high-risk for VRE infection. Antimicrobial stewardship programs should focus on limiting exposure to vancomycin and extended-spectrum penicillins. Disclosures: All authors: No reported disclosures.